When Should ‘Clever’ Cheetah Breed? Seasonal Variability in Prey Availability and Its Effect on Cheetah Reproductive Patterns - Eleesha Annear; Liaan Minnie; Vincent van derMerwe; Graham I. H. Kerley (Ecology and Evolution, 2025)
ABSTRACT Breeding is energetically demanding for female mammals, with maternal and cub nutrition playing a major role in reproductive phases like conception, gestation, lactation and weaning. To meet these demands, adaptations to seasonal shifts in food availability are expected. Some predators may shift prey selection seasonally, optimizing foraging during energetically costly periods. Cheetah, Acinonyx jubatus, prefer adult prey in the dry season when younger prey are scarce but switch to neonate and juvenile prey during the wet season, presumably to optimize foraging during gestation and lactation. Given the wide distribution of cheetah across seasonal (i.e., distinct wet and dry seasons) and aseasonal environments (rainfall throughout the year) and the associated shifts in availability of prey demographic classes, we hypothesized that seasonal prey availability in seasonal systems, but not aseasonal systems, influences the timing of cheetah reproductive phases. Based on the birth dates of cheetahs in seasonal (n = 142) and aseasonal (n = 106) rainfall areas, 58.5% of litters were conceived during the wet season, with 60.6% born in the dry season. In contrast, aseasonal areas showed no seasonality in birth dates. Cheetah reproduction in seasonal environments is driven by the availability of neonate and juvenile prey, with conception and cub independence aligning with peaks in easy‐to‐catch neonates, while lactation coincides with the availability of larger juveniles. Although cheetahs are often viewed as specialized predators with limited ability to adapt to local environmental conditions, our findings suggest they can adjust reproductive patterns in response to prey availability. This adaptability is important as it will allow cheetahs to successfully raise cubs in the face of changing prey reproductive patterns in response to climate change.